2007
DOI: 10.1007/s10534-007-9126-3
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation study of trace element content in colorectal liver metastases and surrounding normal livers by X-ray fluorescence

Abstract: Iron, copper, and zinc are lower in colorectal liver metastases than normal liver. An investigation into the pathways underlying these differences may provide a new understanding of cancer development and possible novel therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Zn homeostasis is coordinated through Zn transporter proteins (ZnT), that include ZIP group increases the intracellular level and cation diffusion facilitator (CDF), and metallothioneines. Gurusamy et al (2008) explain the low levels of Zn found in liver metastases in comparison with normal adjacent tissues as a variation in the levels of Zn transporters and a possible increase in the utilization of Zn by the fast growing tumour tissues. An irregular distribution of Zn in tumours might explain these results.…”
Section: Statistical Comparison Of Datamentioning
confidence: 95%
“…Zn homeostasis is coordinated through Zn transporter proteins (ZnT), that include ZIP group increases the intracellular level and cation diffusion facilitator (CDF), and metallothioneines. Gurusamy et al (2008) explain the low levels of Zn found in liver metastases in comparison with normal adjacent tissues as a variation in the levels of Zn transporters and a possible increase in the utilization of Zn by the fast growing tumour tissues. An irregular distribution of Zn in tumours might explain these results.…”
Section: Statistical Comparison Of Datamentioning
confidence: 95%
“…[7][8][9][10][11] A wide range of applications involves analyses of various types of biomedical specimens including soft tissues, [12][13][14] bones, [15][16][17] and teeth. [18][19][20] The XRF analysis was previously applied to study samples of different body organs such as brain, [8,12,21] prostate, [22] breast, [23] lung, [12] liver, [14,24] heart, [12] or kidneys. [12] It is worth pointing out that multiple physical characteristic of a sample influences the interactions of X-rays with the atoms present in the material analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Iron, copper, and zinc are lower in colorectal liver metastases than in normal surrounding liver (Gurusamy et al 2008;Farquharson et al 2009). The transcription levels of the main zinc efflux transporter ZnT1 is consistently low in colorectal liver metastases compared to normal surrounding liver (submitted for publication).…”
Section: Introductionmentioning
confidence: 99%